DEVELOPMENT OF RICEFIELD MAPPING SYSTEM IN UJUNG PADANG SIMALUNGUN REGENCY - Miftah Hasanah Samosir; Hambali Hambali; Zulfan Efendi (JURTEKSI (Jurnal Teknologi dan Sistem Informasi), 2022)
Abstract: Geographic Information System (GIS) is an information technology that functions to collect, manage, store, and present all data related to the geographical conditions of an area that develops online. Many agencies or companies have not implemented geographic information system technology to obtain the necessary information, one of which is the Simalungun Regency Agriculture Service. The Agriculture Service of Simalungun Regency still does not have a system to utilize rice farming land; it is difficult to find information on rice farming land. The distance of rice farming land is very far. Given the various problems that exist, the purpose of making a Geographic Information System (GIS) can help the Simalungun Regency Agriculture Service in carrying out data processing, to improve performance in uniting agricultural land to be more efficient and effective, and make it easier to obtain information or access to agricultural land data. Paddy. The design of this system uses the waterfall method, which includes software requirements analysis, design, program code generation, testing, support, or maintenance. The results obtained with this system will allow users to see various rice farming lands in Ujung Padang District, Simalungun Regency, accompanied by village names, addresses, number of farmers, harvest production, coordinate points, and website-based agricultural land location routes. Keywords: geographic information system (GIS); mapping; rice farming land Abstrak: Sistem Informasi Geografis (SIG) merupakan suatu teknologi informasi yang berfungsi untuk mengumpulkan, mengelola, menyimpan, dan menyajikan segala data yang berkaitan dengan kondisi geografis suatu wilayah yang berkembang secara online. Banyak berbagai instansi atau perusahaan yang belum menerapkan teknologi sistem informasi geografis untuk memperoleh berbagai informasi yang diperlukan, salah satunya Dinas Pertanian Kabupaten Simalungun. Dinas Pertanian Kabupaten Simalungun masih belum memiliki sistem yang dapat memetakan lahan pertanian padi, sulitnya dalam mengetahui informasi lokasi lahan pertanian padi, jarak tempuh ke lahan pertanian padi yang sangat jauh. Dengan adanya berbagai permasalahan yang ada maka tujuan dibuatnya Sistem Informasi Geografis (SIG) dapat membantu Dinas Pertanian Kabupaten Simalungun dalam melakakukan pengolahan data, untuk meningkatkan kinerja dalam memantau lahan pertanian padi menjadi lebih efesien dan efektif, dan mempermudah dalam memperoleh informasi atau akses terhadap data lahan pertanian padi. Perancangan sistem ini menggunakan metode waterfall yang meliputi analisis kebutuhan perangkat lunak, desain, pembuatan kode program, pengujian, pendukung atau pemeliharaan. Hasil yang diperoleh dengan adanya sistem ini nantinya pengguna dapat melihat berbagai lahan pertanian padi yang ada di Kecamatan Ujung Padang Kabupaten Simalungun yang disertai dengan nama desa, alamat, jumlah petani, produksi panen, titik koordinat, dan rute ke lokasi lahan pertanian padi yang berbasis website.Kata kunci: lahan pertanian padi; pemetaan; sistem informasi geografis (SIG)